2021
DOI: 10.3390/microorganisms9051081
|View full text |Cite
|
Sign up to set email alerts
|

Lactic Starter Dose Shapes S. aureus and STEC O26:H11 Growth, and Bacterial Community Patterns in Raw Milk Uncooked Pressed Cheeses

Abstract: Adding massive amounts of lactic starters to raw milk to manage the sanitary risk in the cheese-making process could be detrimental to microbial diversity. Adjusting the amount of the lactic starter used could be a key to manage these adverse impacts. In uncooked pressed cheeses, we investigated the impacts of varying the doses of a lactic starter (the recommended one, 1×, a 0.1× lower and a 2× higher) on acidification, growth of Staphylococcus aureus SA15 and Shiga-toxin-producing Escherichia coli (STEC) O26:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 56 publications
0
4
0
Order By: Relevance
“…The idea of providing quantitative studies or proofs related to the role of microbial interactions in the microbiological quality and safety of artisanal raw milk products was inspired not only by the history of their production but also by the recent scientific outputs published [10,[39][40][41][42]. According to Schoustra et al [43], traditionally processed foods derived from raw milk may be safe, since adjustment of the doses of the LAB starters can serve as a means of controlling sanitary protection, maintaining bacterial diversity [11,44], and supporting the activity of inherited populations of LAB as well [45]. This is also the case of artisanal lump cheese produced in Slovakian mountain areas and sent for processing for Bryndza cheese after a short 8 to 10 days of ripening [23].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The idea of providing quantitative studies or proofs related to the role of microbial interactions in the microbiological quality and safety of artisanal raw milk products was inspired not only by the history of their production but also by the recent scientific outputs published [10,[39][40][41][42]. According to Schoustra et al [43], traditionally processed foods derived from raw milk may be safe, since adjustment of the doses of the LAB starters can serve as a means of controlling sanitary protection, maintaining bacterial diversity [11,44], and supporting the activity of inherited populations of LAB as well [45]. This is also the case of artisanal lump cheese produced in Slovakian mountain areas and sent for processing for Bryndza cheese after a short 8 to 10 days of ripening [23].…”
Section: Resultsmentioning
confidence: 99%
“…Although most E. coli strains are harmless commensals, some are known to be pathogenic bacteria, causing severe intestinal and extraintestinal diseases in humans. The presence of S. aureus in cheese is associated with post-secretory contamination and it is relevant as it may produce enterotoxins [10][11][12]. In general, the microbiota of artisanal cheese consists of complex assemblages consisting of not only prokaryotic but also fungal populations.…”
Section: Introductionmentioning
confidence: 99%
“…Cheese microorganisms can be deliberately inoculated into the milk or on the cheese surface as starter or secondary cultures, but may also originate from multiple reservoirs, including raw milk (i.e., for raw milk cheeses), brine or salt, or dairy environments (cheese-making equipment and ripening shelves). A distinctive case corresponds to raw milk cheeses as cheese microbiota can be differentiated according to the amount of starter cultures employed during cheese-making and the origin of the raw milk used, at the farm level [ 124 ]. Since milk quality depends on many factors (e.g., animal health status, breed, lactation stage, teat skin, hides, feces management, farm dimension, feeding system, season, farm staff hygiene, and management), recent longitudinal studies have connected some of the main characteristics with farm origin [ 125 , 126 , 127 ].…”
Section: Dna-based Methods For Cheese Origin Authenticationmentioning
confidence: 99%
“…As typical cheese microbiota can be in part acquired from the specific raw materials used, traditional tools, environmental and production conditions, cheese-making process, and geographical area, a comparison between traditional and industrial cheeses may provide additional information to authenticate cheese origin. Noteworthy, some authors have reported that commercial starters, inoculated at ~10 6 CFU/mL, prevent resident microbiota from developing, especially during ripening [ 124 , 142 ]. Overall, milk pasteurization, use of similar commercial starters, similar industrial equipment, and standardized recipes for cheese production are crucial factors that decrease cheese microbial complexity and biodiversity and lead to highly standardized productions.…”
Section: Dna-based Methods For Cheese Origin Authenticationmentioning
confidence: 99%